Bilirubin—albumin binding and neonatal jaundice - Ahlfors, Charles E.; Wennberg, Richard P. (Seminars in perinatology, 2004)
Bilirubin—albumin binding weakens the correlation between the plasma total bilirubin concentration (TBC) and bilirubin encephalopathy (kernicterus), which has led to considerable interest over the years in measuring binding as part of the evaluation of jaundiced newborns. Despite development of several bilirubin—albumin binding tests, technical, ethical, and logistical factors have prevented the prospective studies needed to validate their routine clinical use. Consequently, it has been necessary to adopt aggressive exchange transfusion criteria based on the TBC that require the unnecessary treatment of large numbers of babies to prevent the rare case of kernicterus. Recently, early hospital discharge and arbitrary relaxation of exchange transfusion criteria have resulted in a resurgence of kernicterus. This resurgence and studies showing that nonalbumin bound or “free” bilirubin (B f) correlates better than the TBC with bilirubin toxicity have rekindled interest in bilirubin binding tests. Technological advances in the measurement of B f provide a convenient and economical means for integrating B f measurements into routine clinical practice by determining the bilirubin—albumin binding parameters of various newborn populations.